1999
DOI: 10.1126/science.286.5447.2165
|View full text |Cite
|
Sign up to set email alerts
|

Global Transposon Mutagenesis and a Minimal Mycoplasma Genome

Abstract: Mycoplasma genitalium with 517 genes has the smallest gene complement of any independently replicating cell so far identified. Global transposon mutagenesis was used to identify nonessential genes in an effort to learn whether the naturally occurring gene complement is a true minimal genome under laboratory growth conditions. The positions of 2209 transposon insertions in the completely sequenced genomes of M. genitalium and its close relative M. pneumoniae were determined by sequencing across the junction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
598
2
6

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 825 publications
(619 citation statements)
references
References 27 publications
13
598
2
6
Order By: Relevance
“…This gene has been shown to be nonessential in M. genitalium, but not in M. pneumoniae. However, the vector insertion occurred near the 3 0 -end of the gene, which may not be disruptive to gene function (44,45). The restriction map produced by vector insertion at this location matched our results.…”
Section: Cloning Mycoplasma Genomes That Contain An Integrated Yeast supporting
confidence: 84%
“…This gene has been shown to be nonessential in M. genitalium, but not in M. pneumoniae. However, the vector insertion occurred near the 3 0 -end of the gene, which may not be disruptive to gene function (44,45). The restriction map produced by vector insertion at this location matched our results.…”
Section: Cloning Mycoplasma Genomes That Contain An Integrated Yeast supporting
confidence: 84%
“…Interestingly, we found that in the pilot phase of PSI, the families that were first structurally characterized by the BSGC averaged twice the size of the families characterized by the other 8 pilot centers, containing an average of 262 members, vs. 130 members for the other centers [29]. This is presumably a result of focusing on a minimal organism, as a large fraction of M. genitalium's genes are thought to be essential for life, and therefore nearly ubiquitous across a wide range of species [36].…”
Section: Novelty Of Bsgc Structuresmentioning
confidence: 99%
“…When Hutchison took a sabbatical at TIGR in 1996, he, Smith and Venter began to discuss the idea of developing a cell with the minimum genome needed to survive. Hutchison was already investigating which genes M. genitalium could live without 6 , but he knew that deleting multiple genes simultaneously from this bacterium was technically difficult. The threesome speculated that they might need to synthesize whole candidate genomes and test them in recipient cells.…”
Section: Behind the Walls Of The J Craig Venter Institute Ham Smithmentioning
confidence: 99%